Estimating the prevalence of Hepatitis B Virus infection among age groups of the Libyan population in Tripoli - Soomia Ahmed Al-Haddad; Najla Amer Elyounsi; Abdussalam Ali Ashour; Wasim Khalifa (African Journal of Advanced Pure and Applied Sciences, 2023)
Occult hepatitis B (OBI) poses a significant problem of its transmissibility and prevalence among the community layers; it is considered one of the main causes of hepatic crises including cases of liver cirrhosis and even hepatocellular carcinoma (HCC). This study aims to determine the age group of young people who are most likely infected, which could be used as an indicator to highlight the extent of this problem in the country. Data on HBV patients were gathered from the NCDC, for 36 months from January 2019 to December 2021, was performed the diagnostic test; Enzyme-Linked Immunosorbent Assay (ELISA) on a total number of 3396 participants. As well the data were also analyzed using SPSS version 22. Out of the total of 3396 sample records, about 1681 samples were free of hepatitis B infection (49.50%), and 1715 were positive (50.50%). The number of males infected in the study population was generally 1266, (37.28%) of the total number of 3396 participants in the examination in contrast to 449 female cases (13.23%), with a positivity ratio of 2.82:1. It was the highest frequency of infection with hepatitis B in an age ranging between (31_40), with an average prevalence rate of (33.68%) in the study population. In conclusion, a high rate of hepatitis B positive was identified among the samples participating in the examination, with the highest frequency of infection in the middle age stage. There are also significant gender differences in the burden of hepatitis B virus. A relatively high percentage, requiring further studies and research.